Teaching Factory terhadap Peningkatan Keterampilan Siswa di SMK Negeri 1 Cilegon - Ngadiana Ngadiana; Imas Rohaeti; M. Ashof Azria Azka; Agung Rizky Jamas; Alfi Manarulhuda Huda; Siswo Wardoyo (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
SMK Negeri 1 Cilegon implements the Teaching Factory program to improve students' skills through industry-based learning. This program connects theory with real practice, providing hands-on experience in manufacturing products according to industry standards. Collaboration with PT Indonesia Power enriches students' learning, which has an impact on improving their technical skills and work readiness. However, limited facilities are a major challenge. Nevertheless, this program has succeeded in increasing students' academic scores by 80%-90% and facilitating the absorption of graduates in the workforce.